Antibiotic resistance pattern of waterborne causative agents of healthcare-associated infections: A call for biofilm control in hospital water systems - Sahar Gholipour; Mahnaz Nikaeen; Farzaneh Mohammadi; Davarkhah Rabbani (Elsevier, 2024)
Background: In recent years, the global spread of antimicrobial resistance has become a concerning issue, often referred to as a "silent pandemic". Healthcare-associated infections (HAIs) caused by antibiotic-resistant bacteria (ARB) are a recurring problem, with some originating from waterborne route. The study aimed to investigate the presence of clinically relevant opportunistic bacteria and antibiotic resistance genes (ARGs) in hospital water distribution systems (WDSs). Methods: Water and biofilm samples (n = 192) were collected from nine hospitals in Isfahan and Kashan, located in central Iran, between May 2022 and June 2023. The samples were analyzed to determine the presence and quantities of opportunistic bacteria and ARGs using cultural and molecular methods. Results: Staphylococcus spp. were highly detected in WDS samples (90 isolates), with 33 % of them harboring mecA gene. However, the occurrences of E. coli (1 isolate), Acinetobacter baumannii (3 isolates), and Pseudomonas aeruginosa (14 isolates) were low. Moreover, several Gram-negative bacteria containing ARGs were identified in the samples, mainly belonging to Stenotrophomonas, Sphingomonas and Brevundimonas genera. Various ARGs, as well as intI1, were found in hospital WDSs (ranging from 14 % to 60 %), with higher occurrences in the biofilm samples. Conclusion: Our results underscore the importance of biofilms in water taps as hotspots for the dissemination of opportunistic bacteria and ARG within hospital environments. The identification of multiple opportunistic bacteria and ARGs raises concerns about the potential exposure and acquisition of HAIs, emphasizing the need for proactive measures, particularly in controlling biofilms, to mitigate infection risks in healthcare settings.